Donepezil‐induced oligodendrocyte differentiation is mediated through estrogen receptors. Issue 5 (15th December 2019) - Imamura, Osamu; Arai, Masaaki; Dateki, Minori; Oishi, Kazuhiko; Takishima, Kunio
Abstract: Loss of oligodendrocytes, the myelin‐forming cells of the central nervous system, and subsequent failure of myelin development result in serious neurological disorders such as multiple sclerosis. Using primary mouse embryonic neural stem cells (NSCs), we previously demonstrated that donepezil, an acetylcholinesterase inhibitor developed for the treatment of Alzheimer's disease, stimulates the differentiation of NSCs into oligodendrocytes and neurons, albeit at the expense of astrogenesis. However, the precise mechanisms underlying donepezil‐induced differentiation remain unclear. In this study, we aimed at elucidating the molecular pathways contributing to donepezil‐induced differentiation of mouse‐induced pluripotent stem cell‐derived neural stem cells (miPSC‐NSCs). We used cell‐based reporter gene arrays to investigate effects of donepezil on differentiation of miPSC‐NSCs. Subsequently, we assessed the molecular pathway underlying donepezil action on differentiation of miPSC‐NSCs into mature oligodendrocytes. Donepezil increased the transcriptional activity of estrogen response element under differentiating conditions. Moreover, estrogen receptors α (ERα) and β (ERβ) were highly expressed in MBP‐positive mature oligodendrocytes. The ER antagonist ICI 182, 780 abrogated the number of MBP‐positive oligodendrocytes induced by donepezil, but showed no effect on the differentiation of miPSC‐NSCs into Tuj1‐positive neurons and GFAP‐positive astrocytes. Furthermore, the donepezil‐induced generation of mature oligodendrocytes from miPSC‐NSC was significantly attenuated by antagonists and siRNA targeting ERα and ERβ. In conclusion, we demonstrated, for the first time, that donepezil‐induced oligodendrogenesis is mediated through both ER subtypes, ERα and ERβ. Cover Image for this issue: https://doi.org/10.1111/jnc.14771 . Abstract : The aim of the present study was to elucidate the molecular pathways contributing to donepezil‐induced differentiation of mouse induced pluripotent stem cell‐derived neural stem cells (miPSC‐NSCs). The signaling pathway reporter assay revealed that donepezil increased the transcriptional activity of estrogen response element under differentiating conditions. The estrogen receptor (ER) antagonist ICI 182, 780 abrogated the stimulatory effect of donepezil on oligodendrocyte differentiation of miPSC‐NSCs. Furthermore, the donepezil‐induced generation of mature oligodendrocytes from miPSC‐NSCs was attenuated by selective antagonists and siRNAs for ERα and ERβ. These results indicate that the donepezil‐stimulated oligodendrocyte is mediated through the ER signaling pathway. Cover Image for this issue: https://doi.org/10.1111/jnc.14771 .